On motifs and patterns on Early Trans-Caucasian IIA pottery from Yanik Tepe in northwestern Iran - Summers, Geoffrey D. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
This paper discusses the incised and impressed, white-filled motifs employed in the patterning of Early Trans-Caucasian (ETC) black burnished pottery from the site of Yanik Tepe in North-Western Iran. This site was excavated in the 1960s by Charles Burney and a monograph on the pottery and other finds is now in press. Firstly, an overview of the stratigraphy and context of the pottery from Yanik Tepe is provided. In the following section, which is accompanied by selected illustrations, the techniques employed in making the patterns are described. Next, the motifs themselves are broken down into broad categories of linear, bird and animal, flanking and miscellaneous, before moving on to discussion of combinations of motifs into composite, decorative designs. Brief comments on comparanda of motifs on pottery from within the vast ETC cultural zone precede more general observations on the motifs and discussion of possible interpretations. Conclusions allude to the wider setting of the ETC in relation to contemporaneous Central Iran and Greater Mesopotamia, emphasising yet again the inward-looking and conservative character of ETC culture on the one hand and the development of regional styles on the other.